Eukaryotic ADCY7 catalyzes the production of c-di-AMP to activate the NLRP3 inflammasome - Liu, Qiannv; Tang, Zhiheng; Qian, Yan; Wang, Chunlei; Kong, Chun; Li, Mengqian; Geng, Xiangyang; Zhang, Yan; Cheng, Xiangyun; Ren, Chao; Wang, Kai; Bai, Lin; et al. (Nature chemical biology, 2025)
Toll-like receptor 9 (TLR9) agonists cause activation of nucleotide-binding domain, leucine-rich repeat protein 3 (NLRP3) inflammasomes but the mechanism is not clear. We found that there is a second signal downstream of TLR9 that induces NLRP3 inflammasome activation. Through screening, adenylate cyclase 7 (ADCY7) was found to be an essential regulator of this process. In cells with Adcy7 deficiency, TLR9 agonists were no longer able to activate the NLRP3 inflammasome. ADCY7 not only catalyzes the generation of cyclic adenosine monophosphate (cAMP) but also catalyzes the synthesis of its dimeric form (c-di-AMP). Moreover, c-di-AMP promotes assembly and maturation of the inflammasome by directly binding to NLRP3. Cells with Adcy7 deletion or mutations impacting enzymatic activity cannot produce c-di-AMP. The survival of Adcy7 -deficient mice in acute liver injury was also improved. In summary, we found that ADCY7 is required for NLRP3 inflammasome activation downstream of TLR9 by catalyzing the generation of c-di-AMP, which may serve as a target for controlling inflammatory responses in sterile infections. Cyclic dimeric adenosine monophosphate is found to be a second messenger in eukaryotic cells that is generated by adenylate cyclase 7 and connects Toll-like receptor 9 stimulation to nucleotide-binding domain, leucine-rich repeat protein 3 inflammasome activation.